1990
DOI: 10.4319/lo.1990.35.5.1039
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial exopolymer utilization by a harpacticoid copepod: A methodology and results

Abstract: Exopolymer mucus secretions of bacteria and diatoms are potential foods for benthic animals. These secretions are coincidently ingested by animals during consumption of microbial cells and sediments. The utilization of microbial secretions was investigated with exopolymer derived from a marine bacterium (Pseudomonas sp.) from seagrass beds and a harpacticoid copepod Laophonte sp. from the same habitat. A new technique was developed to examine ingestion, absorption, and absorption efficiencies of these bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 29 publications
2
98
1
1
Order By: Relevance
“…However, the euphausiid Euphausia pacifica can use TEP as a food source (Passow & Alldredge 1999) and bacterial exopolymer coated beads were utilised by the harpacticoid copepod Laophonte sp. (Decho & Moriarty 1990). Passow & Alldredge (1999) found that E. pacifica was feeding on aggregates composed of TEP and nano-sized particles, leading them to conclude that TEP may enable macrozooplankton to feed directly on nano-and picoplankton, thus bypassing the microbial loop.…”
Section: Discussionmentioning
confidence: 99%
“…However, the euphausiid Euphausia pacifica can use TEP as a food source (Passow & Alldredge 1999) and bacterial exopolymer coated beads were utilised by the harpacticoid copepod Laophonte sp. (Decho & Moriarty 1990). Passow & Alldredge (1999) found that E. pacifica was feeding on aggregates composed of TEP and nano-sized particles, leading them to conclude that TEP may enable macrozooplankton to feed directly on nano-and picoplankton, thus bypassing the microbial loop.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biofilm communities are the food source of many types of organisms in aquatic systems such as, invertebrates, including rasping grazers, deposit, planktonic and subdeposit feeders, fish and higher vertebrates (Baird and Thistle, 1986;Decho and Moriarty, 1990;Abreu et al, 2007;Kuwae et al, 2008). Thus, biofilms are considered to represent a trophic link between dissolved compounds in the water column and the higher trophic levels of the ecosystem (Hynes, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TEP may affect the flux of organic carbon from the euphotic layer to the deep ocean, and help to explain the discrepancy between observed vertical flux and those predicted by aggregation-sedimentation models (Jackson 1990, Hill 1992, Logan et al 1995. In addition TEP may be consumed by protozoans and copepods (Decho & Moriarty 1990, Shimeta 1993, Tranvik et al 1993 and, thus, it may represent an alternative pathway for the transfer of carbon and energy from dis-ABSTRACT: Transparent exopolymer particles (TEP) are considered to be generated abiotically from dissolved extracellular polysaccharides released mainly by phytoplankton. TEP may affect the aggregation rate of particles and therefore influence the flux of organic carbon to the deep ocean.…”
Section: Introductionmentioning
confidence: 99%